The Concept of Halal Sustenance Thayyiban According to Members of the National Police (Case Study) for the Red Market Police Dormitory Reviewed from Tafsir Al-Azhar - Siregar, Khairul Aula; Matondang, Husnel Anwar (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
Abstract This study aims to examine the understanding of Indonesian National Police (Polri) members regarding the concept of halal and sound sustenance (halalan thayyiban), its practical implementation, challenges encountered, and its relevance to Buya Hamka’s Tafsir Al-Azhar. The research employs a qualitative case study design, combining theological-normative and sociological approaches. The findings reveal that Polri members at the Pasar Merah Police Dormitory generally possess a good understanding, though with varying depth. Halal and sound sustenance is interpreted as lawful and blessed income, applied through honesty, professionalism, and simplicity. Challenges arise from economic pressures, permissive culture, and weak supervision. Tafsir Al-Azhar emphasizes that sustenance must be halal in accordance with sharia and thayyib in moral and spiritual dimensions. Implementing these values positively impacts integrity, professionalism, public trust, and quality of life, positioning Polri members as role models in fostering a clean and just work culture. Keywords: Halalan, Thayyiban, Al-Azhar Interpretation.AbstrakPenelitian ini bertujuan untuk mengkaji pemahaman anggota Polri mengenai konsep rizki halal dan baik (halalan thayyiban), praktik penerapannya, tantangan yang dihadapi, serta relevansinya dengan Tafsir Al-Azhar karya Buya Hamka. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan studi kasus, memadukan pendekatan teologis-normatif dan sosiologis. Hasil penelitian menunjukkan bahwa pemahaman anggota Polri di Asrama Polisi Pasar Merah umumnya baik, meskipun tingkat kedalamannya bervariasi. Rezeki halal dan baik dipahami sebagai rezeki yang sah menurut syariat dan diberkahi, serta diwujudkan melalui kejujuran, profesionalisme, dan kesederhanaan. Hambatan yang muncul terkait tekanan ekonomi, budaya permisif, dan lemahnya pengawasan. Tafsir Al-Azhar menekankan pentingnya rezeki halal secara syar’i dan thayyib secara moral-spiritual. Implementasi nilai ini berdampak positif terhadap integritas, profesionalisme, kepercayaan publik, serta kualitas hidup, sehingga menjadikan anggota Polri teladan dalam budaya kerja yang bersih dan adil. Kata Kunci: Halalan, Thayyiban, Tafsir Al-Azhar.